ANALISIS LITOTES DALAM DRAMA MACBETH KARYA WILLIAM SHAKESPEARE: KAJIAN SOSIOPRAGMATIK - Fauzi, Mohd.; Junaidi, Junaidi; Islami, Qori (JURNAL PUSTAKA BUDAYA, 2017)
AbstractThis research analyzes Litotes Language in the Macbeth Drama Written by William Shakespeare: Sociopragmatics approach. Thus, the objective of this analysis is to show and to analyze how the main characters use the litotes language in Macbeth. To reach that objective, this analysis applies sociopragmatics and litotes to gain the data. In analyzing this research, the writer applies a descriptive analysis method in which the result of the analysis will be described clearly. The results shown that many words and phrases used by the main characters in the Macbeths.Keywords: Macbeth, Litotes, DramaAbstrakTulisan ini menganalisis Bahasa Litotes yang terdapat dalam film Macbeth yang ditulis oleh William Shakespeare. Tujuan penelitian ini adalah untuk menganalisis bentuk, fungsi, dan makna bahasa Litotes yang digunakan oleh tokoh utama karya ini. Untuk mencapai tujuan itu, kajian ini menerapkan kajian sosiopragmatik. Kajian ini menerapkan metode deskriptif analisis dimana hasil analisis akan dideskripsikan dengan jelas. Dari deskripsi yang dijabarkan akan memperlihatkan bagaimana tindak tutur yang digunakan oleh tokoh utama karya ini dalam menghadapi masalah-masalah yang menimpanya. Kata Kunci: Macbeth, Litotes, Drama